Long-range chemical sensitivity in the sulfur K-edge X-ray absorption spectra of substituted thiophenes - George, G.; Hackett, Mark; Sansone, M.; Gorbaty, M.; Kelemen, S.; Prince, R.; Harris, H.; Pickering, I. (American Chemical Society, 2014)
© 2014 American Chemical Society. Thiophenes are the simplest aromatic sulfur-containing compounds and are stable and widespread in fossil fuels. Regulation of sulfur levels in fuels and emissions has become and continues to be ever more stringent as part of governments' efforts to address negative environmental impacts of sulfur dioxide. In turn, more effective removal methods are continually being sought. In a chemical sense, thiophenes are somewhat obdurate and hence their removal from fossil fuels poses problems for the industrial chemist. Sulfur K-edge X-ray absorption spectroscopy provides key information on thiophenic components in fuels. Here we present a systematic study of the spectroscopic sensitivity to chemical modifications of the thiophene system. We conclude that while the utility of sulfur K-edge X-ray absorption spectra in understanding the chemical composition of sulfur-containing fossil fuels has already been demonstrated, care must be exercised in interpreting these spectra because the assumption of an invariant spectrum for thiophenic forms may not always be valid.